Adiposity, but not Obesity, Is Associated With Arterial Stiffness in Young Nulliparous Women. (June 2018) - Phillips, Julie; McBride, Carole A.; Morris, Erin; Crocker, Abigail M.; Bernstein, Ira
Subclinical vascular dysfunction is increasingly recognized as an independent risk factor for cardiovascular events and adverse pregnancy outcomes. The evidence linking indices of obesity and vascular dysfunction is mixed. As an example, some data suggest that adiposity may be a better predictor of endothelial dysfunction than body mass index (BMI). The aim of the current study is to compare the association of obesity, as evaluated by BMI, and a direct measure of body fat to biophysical parameters of vascular function including flow-mediated vasodilation and pulse wave velocity (PWV) in healthy nulliparous reproductive-age women. This is a secondary analysis of data collected as a prospective study of prepregnancy physiology in healthy, nulliparous women. Body mass index was calculated as weight (kg)/height (m 2 ). Total and android body fat were calculated by dual-energy X-ray absorptiometry. Brachial PWV and flow-mediated vasodilation were assessed ultrasonographically. Seventy-nine women were evaluated. Mean BMI was 24.4 (5.4) kg/m 2, and 15% of women were obese (BMI ≥ 30 kg/m 2 ). In contrast, 39% were considered to have excess adiposity, with ≥39% android body fat. Brachial PWV was associated with increased adiposity, but not obesity. We found no differences in flow-mediated dilation associated with either BMI or body fat. Adiposity may be superior to BMI in identifying women with vascular dysfunction at increased risk of adverse pregnancy outcome and cardiovascular disease. Proper identification may allow implementation of prevention strategies to improve perinatal outcomes and maternal health.